THE CHANGE OF UPPER TRAPEZIUS AND SERRATUS ANTERIOR FOR VISUAL INFORMATION DURING SHOULDER FULL FLEXION IN FORWARD HEAD POSTURE: PRELIMINARY STUDY - Liwen Xu; Dae-Hyun Kim; Tae-Ho Kim (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2020)
The purpose of this study was to identify the effects of visual information for head posture on muscle activity of upper trapezius and serratus anterior and a ratio of serratus anterior to upper trapezius during shoulder full flexion test in subjects with forward head posture.